Declining insulin sensitivity is a key pathological contributor to dysglycemia: a longitudinal validation study in the Korean genome and epidemiology study - Kim, Doohwa; Kim, Jinmi; Im, Myungsoo; Ryang, Soree; Kim, Minsoo; Kim, Yeong Jin; Kim, In Joo; Kim, Young Jin; Kang, Hyuk; Chung, Stephane T.; Sherman, Arthur S.; Kim, Sang Soo; et al. (Frontiers in Endocrinology, 2026)
BackgroundThe role of worsening insulin resistance (IR) in type 2 diabetes (T2D) progression among lean individuals is not well understood. We examined whether declining insulin sensitivity (IS), independent of beta-cell function (BCF), is associated with diabetes progression.MethodsIn a 10-year longitudinal Korean cohort with normal glucose tolerance (N = 2,810; age 50 ± 8y; BMI 24.1 ± 2.8 kg/m²), participants underwent biannual oral glucose tolerance tests. Longitudinal changes in IS, BCF, BMI, and fat mass were evaluated. Participants were stratified by baseline BCF (low/high), diabetes progression status (non-progressors [Non-p], progressors to prediabetes [PreDM-p], or T2D [T2D-p] over time), and degree of IS decline (large/small).ResultsBoth T2D-p and PreDM-p showed greater IS decline than Non-p. At baseline, PreDM-p had IS comparable to T2D-p, but T2D-p declined more steeply. T2D-p and PreDM-p also had lower BCF at baseline, which remained low. Across baseline BCF groups (high/low), greater IS decline was consistently associated with higher risk of progression (all P<0.001). The effect size of IS decline exceeded that of BCF deterioration.ConclusionsDeclining IS, independent of BCF, is associated with progression to T2D in lean Koreans. Preserving IS through lifestyle interventions is crucial for diabetes prevention, particularly in those with low BCF. Insulin resistance, β-cell function, disposition index, oral glucose tolerance test, body mass index.